PELAKSANAAN HUKUM HAK ASASI MANUSIA TERHADAP PELAKU LESBIAN GAY BISEKSUAL TRANSGENDER (LGBT) DI INDONESIA - Maulana Maulana (SOL JUSTICIA, 2019)
At present, human rights as particularism are replaced by universal human rights because "in the concept of modern human rights, the influence of liberalism can be seen in passive civil rights, namely individual freedom from State interference. This study discusses how the application of the law of rights human rights as a means of social control over transgender gay lesbians (LGBT) in Indonesia and how the treatment and views of the community towards bisexual transsexual gay men (LGBT) in Indonesia The method used in this study is a normative research method in which the material used is in the form of literature , books on law, legal dictionaries, and other literary materials.The result of this research is that human rights in Indonesia apply universally to all citizens, regardless of social and economic status and gender.Today, LGBT cases in Indonesia are opposed LGBT people get treatment who deserve even some of their rights must be confiscated. In addition, there are also various forms of discrimination that make LGBT people experience difficulties in living their lives. When viewed from the perspective of human rights as relative-particularistic, it is clear that Indonesia strictly forbids LGBT because it is not in accordance with Pancasila and is contrary to Indonesian cultural values. However, in the context of Human Rights Law, LGBT people must obtain the same rights as other citizens. Human Rights Law in Indonesia protects all citizens' rights, without exception, especially their civil rights. Keywords: Human Rights, Implementation, Transgender.